Analytical simulation for couple stress Williamson nanofluid flow and heat transfer towards a shrinking surface with slip and viscous dissipation effects - Rehman, Ali; Khun, Ma Chau; İnç, Mustafa; Chou, Dean; Rezapour, Shahram (Wiley-V C H Verlag Gmbh, 2025)
This research work simulates analytically the flow and heat transfer properties of a couple stress Williamson nanofluid (WN) across a shrinking surface, accounting for the effects of slip and viscous dissipation. The Williamson and couple stress fluid model, using blood as the base fluid, tackles non-Newtonian behavior. When there are slip conditions at the boundary, they change the velocity profile. Titanium dioxide and silver are used as nanoparticles, and blood is used as a base fluid for the formation of two different nanofluids. The study also looks at the role of viscous dissipation, which changes mechanical energy into thermal energy and adds to the energy equation. We use the homotopy analysis method (HAM) to analytically solve the governing nonlinear PDEs, which similarity transformations have converted into nonlinear ODEs. We thoroughly examine the effects of significant parameters, such as the couple stress parameter, Williamson fluid parameter, slip length, nanoparticle volume friction, and Eckert number (EN), on the temperature and velocity fields (VF). The results show how these factors interact in complex ways, giving us new ways to think about controlling and managing the heat of non-Newtonian nanofluid flows in engineering settings.
Keywords: Stagnation-Point Flow; Mass-Transfer; Stretching Sheet; Suction